Dietary protein and bone health: towards a synthesised view. Issue 2 (13th May 2021) - Darling, Andrea L.; Millward, D. Joe; Lanham-New, Susan A.
Abstract : The present paper reviews published literature on the relationship between dietary protein and bone health. It will include arguments both for and against the anabolic and catabolic effects of dietary protein on bone health. Adequate protein intake provides the amino acids used in building and maintaining bone tissue, as well as stimulating the action of insulin-like growth factor 1, which in turn promotes bone growth and increases calcium absorption. However, the metabolism of dietary sulphur amino acids, mainly from animal protein, can lead to increased physiological acidity, which may be detrimental for bone health in the long term. Similarly, cereal foods contain dietary phytate, which in turn contains phosphate. It is known that phosphate consumption can also lead to increased physiological acidity. Therefore, cereal products may produce as much acid as do animal proteins that contain sulphur amino acids. The overall effect of dietary protein on physiological acidity, and its consequent impact on bone health, is extremely complex and somewhat controversial. The consensus is now moving towards a synthesised approach. Particularly, how anabolic and catabolic mechanisms interact; as well as how the context of the whole diet and the type of protein consumed is important.